Analysis of Drug Waiting Time at the Pharmacy Depot at the Outpatient Installation at the Bangkinang Regional General Hospital, Kampar Regency, in 2023 - Firdaus Pratama Sabri*; Zulmeliza Rasyid (Universitas Syiah Kuala, 2023)
To realize safe and quality health services, every hospital is required to meet the National Indicators for the Quality of Health Services which is one of the tools for assessing and evaluating hospitals in maintaining and improving the quality of health services in accordance with Regulation of the Minister of Health Number 30 of 2022, one of the indicators Hospital service qualities is patient satisfaction. Patient satisfaction plays an important role in determining the quality and quality of health services provided by health care facilities. The extension of waiting time for drug services is a matter of concern to the public and is seen as one of the things that has the potential to cause patient dissatisfaction. The purpose of this study was to analyze the waiting time for prescription services at the pharmacy depot at the Outpatient Installation at Bangkinang Regional General Hospital, Kampar Regency in 2022. This study used a qualitative research method through in-depth interviews with 8 informants, observation , and document reviews. The research results obtained are that the number of staff on duty at the Outpatient Pharmacy Depot is still lacking so that the workload of officers is excessive, while prescription writing is currently being carried out using electronic and manual prescriptions with quite many recipes being served every day . Bangkinang Hospital already has a good SPO for prescription drug services to be used as a reference for officers, while the room for the Outpatient Pharmacy Depot is narrow, which hinders the movement of officers in providing services. The conclusion of this study is that the man factor, the tool factor and the material factor are inadequate and do not comply with the provisions